2015
DOI: 10.1080/10408398.2014.972498
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Red/Processed Meat and Colorectal Carcinoma: Possible Mechanisms Underlying the Significant Association

Abstract: Epidemiology and experimental studies provide an overwhelming support of the notion that diets high in red or processed meat accompany an elevated risk of developing pre-neoplastic colorectal adenoma and frank colorectal carcinoma (CRC). The underlying mechanisms are disputed; thus several hypotheses have been proposed. A large body of reports converges, however, on haem and nitrosyl haem as major contributors to the CRC development, presumably acting through various mechanisms. Apart from a potentially higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 232 publications
(351 reference statements)
0
14
0
Order By: Relevance
“…In 2007, the World Cancer Research Fund considered intake of red and processed meat to be a convincing risk factor for CRC [2], and in 2015 the International Agency for Research on Cancer (IARC) classified processed meat carcinogenic to humans (Group 1) and red meat as probably carcinogenic to humans (Group 2A) [3]. Even though several experimental studies in rodents have suggested a relationship between red meat intake and CRC [46], the role of red meat in initiation, promotion and progression of CRC is not clarified. Interestingly, animal studies were not able to reproduce epidemiological findings until basal diets were modified to reflect a “Western style diet” characterized by high fat, low calcium, and low antioxidants [7, 8], indicating complex mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, the World Cancer Research Fund considered intake of red and processed meat to be a convincing risk factor for CRC [2], and in 2015 the International Agency for Research on Cancer (IARC) classified processed meat carcinogenic to humans (Group 1) and red meat as probably carcinogenic to humans (Group 2A) [3]. Even though several experimental studies in rodents have suggested a relationship between red meat intake and CRC [46], the role of red meat in initiation, promotion and progression of CRC is not clarified. Interestingly, animal studies were not able to reproduce epidemiological findings until basal diets were modified to reflect a “Western style diet” characterized by high fat, low calcium, and low antioxidants [7, 8], indicating complex mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…Although meat has been classified as a Group 1 carcinogen, the same category as tobacco smoke and asbestos, WHO does not conclude that meat should be banned, and recommends to avoid any paranoia or psychosis, because even though the risk increases with the amount, bacon or hot dogs are much less carcinogenic than smoking (1 million deaths/ year caused by tobacco, 34.000 deaths/year caused by processed meat) (***, 2015c). Many hypotheses of the carcinogenic effect of meat are advanced: a) disruption of gut microbiota/microbiome by protein excess (Gagnière et al, 2016); b) meat is a pro-inflammatory food by heme iron (Hammerling et al, 2016;Guéraud, 2015), and arachidonic acid, an essential omega-6 fatty acid -the origin of many pro-inflammatory factors (cancer is related to inflammation in all phases) (Harris et al, 2009); c) the fat from meat needs bile acids for digestion, because gut bacteria turn these bile acids into cancer-promoting factors called secondary bile acids (e.g. lithocholic acid) which are very aggressive for the colon, and, secondly, meat fosters the growth of bacteria that cause carcinogenic secondary bile acids to form (Ayouz et al, 2014); and d) heating meat at high temperatures produces many highly toxic end products.…”
Section: Meatmentioning
confidence: 99%
“…Since the International Agency for Research on Cancer (IARC) released their monograph stating that consumption of red and processed meats are linked to colorectal cancer (CRC) in 2015, research regarding this topic has increased, particularly since the mechanisms leading to these links remain partly unknown [1]. The most commonly proposed factors underlying the link between consumption of red/processed meat and CRC have been attributed to the following, partly overlapping, mechanisms: (I) An increase in oxidative or N-nitrosation load leading to lipid oxidation and DNA adducts in the intestinal epithelium, respectively; (II) stimulation of proliferation of the epithelium by heme or other food metabolites acting either directly or following conversion, e.g., heterocyclic amines (HCAs) and polycyclic aromatic hydrocarbons (PAHs) through high-temperature cooking; and (III) pro-malignant processes triggered by a higher inflammatory response, e.g., by a process where N-glycolylneuraminic acid (Neu5Gc) is involved in developing xenosialitis, an inflammatory syndrome inducing cancer formation and progression [2,3].…”
Section: Introductionmentioning
confidence: 99%